Мне бы решить по фасту

Мне бы решить по фасту
Гость
Ответ(ы) на вопрос:
Гость
[latex]\left (\sqrt{ab}- \frac{ab}{a+\sqrt{ab}} \right ): \frac{a^2b}{a-b} =\left ( \frac{\sqrt{ab}\cdot (a+\sqrt{ab})-ab}{a+\sqrt{ab}} \right ): \frac{a^2b}{(\sqrt{a}-\sqrt{b})(\sqrt{a}+\sqrt{b})} =\\\\= \frac{a\sqrt{ab}+ab-ab}{\sqrt{a}\cdot (\sqrt{a}+\sqrt{b})} \cdot \frac{(\sqrt{a}-\sqrt{b})(\sqrt{a}+\sqrt{b})}{a^2b} = \frac{a\sqrt{a}\cdot \sqrt{b}}{\sqrt{a}} \cdot \frac{\sqrt{a}-\sqrt{b}}{a^2b} =\\\\= \frac{\sqrt{a}-\sqrt{b}}{a\sqrt{b}} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы